PENERAPAN PENDEKATAN PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKA KETERAMPILAN MEMBACA WACANA NARASISISWA KELAS IV SD NEGERI 9 TENGGAYUNKECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Hana Linda; Syahrilfuddin Syahrilfuddin; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated poor reading skills narrative discourse fourth grade students of SD Negeri 9 Tenggayun numbering 33 students with KKM 70 only 12 (36.36%) students were above the KKM, while 21 (63.64%) students under KKM, with an average of 60.06. Based on these problems, researchers conducted the study with the form of research using Action Research (PTK) by applying a contextual learning approach. keterammpilan students increased from an average of 60.06 risen early on the first UH becomes 70.61. While UH II increased again to 77.27. The percentage of teacher activity cycle I meeting 1 of 60.7% to the category of pretty, meeting 2 of 64.3% in both categories. In the second cycle of 71.4% first meeting with a good category and at the meeting of 2 of 82.1% with very good category. Student activity cycle I meeting 1 of 57.1% to the category fairly and meeting 2 of 60.7% to the category enough. Cycle II meeting 1 of 71.4% and a meeting with either category 2 by 83.9% with very good category. Classical completeness in the first cycle and the second cycle is reached. Application of Contextual learning approach can improve the reading skills of narrative discourse fourth grade students of SD Negeri 9 Tenggayun Bengkalis district of Bukit Batu subdistrict.Keywords: Contextual Learning Approach, reading skills narrative discourse